Revealing the meaning of trust in Leadership in the context of a public hospital - Yañez Gallardo, Rodrigo (2018)
Research on interpersonal trust has been poorly analyzed from the conceptualization of Latin American workers. This research aimed to understand the meaning that health officials attribute to trust in direct leadership. A descriptive-analytical design was used, as well as a phenomenological approach for the information analysis. 65 officials of a public hospital were interviewed. A total of 5 categories were obtained, from which the main two covered 81% of the dimensions. The two main categories are related to “having good communication” and “support when there are problems”. Thus, a model of dyadic trust emerges, which is constructed especially from personalized links in which the officials perceive protection, probably related to a paternalist leadership with the bosses. Findings are consistent with the Latin American organizational culture.